KRISIS SAINS MODERN KRISIS DUNIA MODERN DAN PROBLEM KEILMUAN - Anggit Fajar Nugroho (Jurnal Penelitian Agama, 2018)
Abstract: Modern science, besides its advantages, also has weaknesses, such as its reductionist nature, claims of science objectivity, utilitarian nature, and some others. In this global era, science can cause crises, like the depletion of the ozone layer, which is caused by chemicals released by objects of scientific products. In addition to the crisis, science also receives criticism from various groups who view science as not only providing benefits but also creating dangers that cannot be considered trivial. In the arena of crisis and criticism of modern science, the paradigm of modern science is revealed which is nothing but the philosophy of mechanistic materialism and at the same time the dominance of the materialistic paradigm collapses. Thus it is time for Islamic scientists to provide the paradigm of religious science as a new paradigm for post-modern science in the new millennium. It is hoped that Islam can once again become a religious foundation through the Islamic paradigm of science for Islamic science. Keywords: science crisis, modern world, and scientific problems.